Program Pendampingan Literasi, Numerasi, Adaptasi Teknologi dan Administrasi di SD Inpres Mauloo - Kartini Kari (Universitas Muhammadiyah Mataram, 2023)
Abstract: The Teaching Campus Program is one of the MBKM programs launched by the Ministry of Education and Culture of the Republic of Indonesia as a solution for improving the quality of education during a pandemic. Its purpose is to teach, assist with technology adaptation, and assist with school administration and teachers. One of the schools targeted by the Teaching Campus program is SD Inpres Mauloo which is located in Mbengu Village, Kec. Paga, Kab. Sikka, Prov. East Nusa Tenggara. This program involves all students who are selected as campus teaching participants to assist the school in the teaching process. The purpose of student participation in the Teaching Campus program is so that students can add to relationships, add experience outside the world of lectures, develop students' insights, character and soft skills, and increase the role and real contribution of tertiary institutions and students in the development of education in Indonesia. The aim of the research was to see the extent to which students' literacy and numeracy abilities, students' and teachers' technology adaptation abilities and school administration improvements. The research method used is a qualitative method. The results of the study show that the existence of a teaching campus program is very helpful for the learning process.Abstrak: Program Kampus Mengajar merupakan salah satu program MBKM yang dicanangkan oleh Kementrian Pendidikan dan Kebudayaan Republik Indonesia menjadi salah satu solusi bagi peningkatan mutu pendidikan pada masa pandemi. Tujuannya adalah untuk mengajar, membantu adaptasi teknologi, dan membantu administrasi sekolah dan guru. Salah satu sekolah yang menjadi sasaran dari program Kampus Mengajar adalah SD Inpres Mauloo yang terletak di Desa Mbengu, Kec. Paga, Kab. Sikka, Prov. Nusa Tenggara Timur. Program ini melibatkan seluruh mahasiswa yang terpilih sebagai peserta kampus mengajar untuk membantu pihak sekolah dalam proses Mengajar. Tujuan dari keikutsertaan mahasiswa dalam program Kampus Mengajar ini adalah agar mahasiswa dapat menambah relasi , menambah pengalaman di luar dunia perkuliahan , mengembangkan wawasan , karakter dan soft skills mahasiswa , serta meningkatkan peran dan kontribusi nyata perguruan tinggi dan mahasiswa dalam pembangunan pendidikan di Indonesia. Tujuan penelitian adalah untuk melihat sejauh mana kemampuan literasi dan numerasi siswa, kemampuan adaptasi teknologi siswa dan guru serta pembenahan administarasi sekolah. Metode penelitian yang digunakan adalah metode kualitatif. Hasil penelitian menunjukan bahwa dengan adanya program kampus mengajar ini sangat membantu proses pembelajaran.